A Case Report on Multiple Developmental Craniovertebral Junction Anomalies Associated with Fusion of the Third and Fourth Cervical Vertebrae - Himanshu Mishra; Amit Kumar; Hitnarayan Prasad; Sanjay Kumar Suman (Advanced Concepts in Medicine and Medical Research Vol. 9, 2023)
This chapter discusses multiple developmental craniovertebral junction anomalies associated with fusion of the third and fourth cervical vertebrae. Craniovertebral junction (CVJ) is formed by the occipital condyles of the skull, atlas (C1), and axis (C2). CVJ anomalies are a complex group of disorders with a variable course and complicated line of management. A cross-sectional imaging is indispensable for the evaluation of CVJ as it may unmask pathologies unsuspected by clinical evaluation and conventional radiography. A 25-year-old male patient presented with complaints of low- grade neck pain, weakness of both the lower limbs, and fecal incontinence. According to the patient, the symptoms began at the age of 13 years and had progressed gradually, so that, now, he was bedridden for 6 months. The multiple developmental CVJ anomalies include fusion defects of anterior and posterior arches of C1, os odontoideum, atlantoaxial subluxation (with compression of the cervical cord at the cervicomedullary junction), and fusion of C3 and C4 vertebral bodies as well as posterior elements.